2016
DOI: 10.17554/j.issn.2311-5106.2016.03.158
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of Medication-Related Risks for Falls and Osteoporosis at a Hospital Network: A Post-hoc Analysis

Abstract: pump inhibitors carried a 14% increased relative risk of a fracture in this cohort (P = 0.218). There was also high prevalence of pre-existing fractures, pulmonary disease, heart failure and strokes in the study population. CONCLUSION: Falls risk assessment in relation to medication use is frequently inaccurate and is not done at all for a significant proportion of patients. The use proton pump inhibitors and medication-related risks for falls and osteoporosis treatment can be improved with potential for hospi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2018
2018
2018
2018

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 23 publications
0
2
0
Order By: Relevance
“…Another class identified as a PIM is PPI therapy, which is frequently used beyond the primary indication and is associated with an increased risk of multiple adverse events including chronic kidney disease, dementia, osteoporotic fractures, micronutrient deficiencies, as well as bacterial infections of the bowel and lungs, and mortality when used beyond a year [17,18,19].This class of drugs is commonly identified as a target for deprescribing [18], and should be reviewed at every healthcare team-patient interaction; especially as previous studies have identified that up to 40% of patients have no documented reason to use PPIs [19].We have previously shown in a cohort of patients admitted to the same tertiary hospital for falls, that PPI use was over 40%, with 42.9% use among those who sustained an osteoporotic fracture, and as high as 56.2% in those with a fracture while on osteoporosis treatment with antiresorptive therapy [20]. The fact that over half the population in this general medical cohort was on PPI therapy is troubling given the known long term complications, not to mention the unnecessary addition to the overall pill burden and the potential to compromise the efficacy of bisphosphonate therapy in an already high risk population [20].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Another class identified as a PIM is PPI therapy, which is frequently used beyond the primary indication and is associated with an increased risk of multiple adverse events including chronic kidney disease, dementia, osteoporotic fractures, micronutrient deficiencies, as well as bacterial infections of the bowel and lungs, and mortality when used beyond a year [17,18,19].This class of drugs is commonly identified as a target for deprescribing [18], and should be reviewed at every healthcare team-patient interaction; especially as previous studies have identified that up to 40% of patients have no documented reason to use PPIs [19].We have previously shown in a cohort of patients admitted to the same tertiary hospital for falls, that PPI use was over 40%, with 42.9% use among those who sustained an osteoporotic fracture, and as high as 56.2% in those with a fracture while on osteoporosis treatment with antiresorptive therapy [20]. The fact that over half the population in this general medical cohort was on PPI therapy is troubling given the known long term complications, not to mention the unnecessary addition to the overall pill burden and the potential to compromise the efficacy of bisphosphonate therapy in an already high risk population [20].…”
Section: Discussionmentioning
confidence: 99%
“…The psychotropic group of medications was commonly used in the studied population with over a quarter of the patients taking antidepressants and almost in one in 5 patients using sedatives. Psychotropic medications are associated with falls and fracture risk [3,6,8,20], with antidepressant use being a strong association with a falls history in the studied cohort. The use of antipsychotics preadmission was found to be associated with a higher inpatient mortality in our study, with previous research identifying that this class of medications is frequently overused with poor efficacy for management of delirium and known increased risk of stroke [3,20].…”
Section: Discussionmentioning
confidence: 99%